QUALITY OF LIFE IN PATIENTS WITH TOTAL HIP REPLACEMENT - A PILOT STUDY - Denitsa Grozdeva; Evgenia Vladeva; Gergana Nenova; Veselinka Nestorova (Peytchinski Publishing, 2023)
Introduction: Total hip joint replacement is the most frequent surgery intervention for the treatment of degenerative diseases. Rehabilitation after surgery plays an instrumental role for functional recovery and returning to the labor market or daily activities. Although postsurgical pain and function improvement are widely explored, there is no focus on other aspects of life influenced by total hip replacement. The most used instruments for quality of life measuring are specific ones, but a number of disadvantages lead to the need for broad-ranged concept. Aim: to evaluate the quality of life in total hip replacement patients undergoing a personalized rehabilitation program and to define its influence on physical, psychological, social and environmental dimensions of life. Material and methods: A personalized rehabilitation program was applied for 7 days in 19 patients who underwent conventional total hip replacement surgery. Quality of life was measured on the first and the last day of their hospital stay by using the WHOQOL-BREF questionnaire. Results: Significantly improved QOL total score was reported for all participants after the rehabilitation course. Comparing QOL in domains shows statistically significant improvement in all of them except "Social relationships." Conclusion: Early rehabilitationwith an individual approach could achieve QOL improvement in different life aspects of THR patients. WHOQOL-BREF could be a useful tool for quality of life assessment after rehabilitation surgical interventions such as total hip replacement.